Vůně pardála…: Peripatetická reflexe olfaktorické problematiky ve stínu dnešní vědy - Bartoš, Hynek (Lidé města, 2006)
In one of the past issues of this magazine (Lidé města, 14, 2004/2) we had the opportunity to get acquainted with views of present biological anthropology on some basic questions regarding origins and significance of human sense of smell. J. Havlíček’s study titled “Recognize them by scent” and subtitled “Individual recognition by smell” attempts to critically overview the modern biological studies on scent identification. In both this and in the previous article on olfactory topic, J. Havlíček draws from up-to-date scientific literature and shows what type of research is currently “in”. Due to the leading role of evolutionary biology on the current natural sciences scene, it is no surprise that the biggest interest of researchers includes topics that are closely related to reproduction (e.g. ability to identify sexual partners and relatives, identification of sensed person’s sex, change of scent and smell sensitivity during fertility, analysis of sexual attractants, etc.).Havlíček explains ways of biological thinking typical primarily for Anglophone scientific community of the last decades of the twenties century that focuses most of its research activity on problems of sexual selection and reproductive strategies. At the same time, this research tradition is typically convinced that published views are very perishable and the value of information is judged rather by its freshness than its age. This study is intended as a kind of pendant balancing this specific way of thinking and drawing our attention to very long tradition of examination of smell, odors, and scent.